KUALITAS BIOPELET DARI CAMPURAN SERBUK KAYU KARET (Hevea brasiliensis Muell. Arg) DAN TANDAN KOSONG KELAPA SAWIT (Elaeis guineensis Jacq.) - Muhammad Gerry Surya Perdana; Violet Burhanuddin; Siti Hamidah (Jurnal Sylva Scienteae, 2026)
The aim of this research is to determine the quality of biopellets made from unproductive rubber sawdust and empty oil palm bunch waste including water content, density, ash content, volatile matter, bound carbon, calorific value and to find out which biopellet quality composition is best suited. SNI 8021:2014. The test results showed that the water content of all treatments met the standards, while other parameters (density, ash content, volatile matter, bound carbon) did not meet the standards. Meanwhile, for the calorific value, only treatment A (100% rubber wood) can meet the standard, where based on statistical tests this treatment is very significantly different from other treatments. These results show that biopellets made from 100% rubber wood are biopellets with the best treatment. The research results showed that biopellets consisted of composition A (100% rubber wood); composition B (75% rubber wood + 25% empty oil palm bunch); composition C (50% rubber wood + 50% empty oil palm bunch); composition D (25% rubber wood + 75% empty oil palm bunch); composition E (100% empty oil palm bunch), respectively water content values (7.99%; 7.89%; 7.09%; 7.09% ; 7.44%), density (0.32 g /cm3; 0.35 g/cm3; 0.33 g/cm3; 0.34 g/cm3; 0.39 g/cm3), ash content (1.60%; 2.17%; 2.11%; 2.70%; 4.12%), volatile matter (90.09%; 89.55%; 89.72%; 89.96%; 89.19%), bound carbon (8.23%; 8, 20%; 8.09%; 7.86%; 6.62%) and calorific value (4004.43 cal/g; 3961.25 calg; 3947.12 cal/g; 3867.85 cal/g; 3844, 75 cal/g).